Bed Shear Stress and Near‐Bed Flow Through Sparse Arrays of Rigid Emergent Vegetation - J. Aliaga; J. Aberle (Water Resources Research)
Abstract Vegetation is an essential component of natural rivers and has significant effects on flow and morphodynamic processes. Although progress has been made in characterizing flow resistance in vegetated flows, the impact of vegetation on bed shear stress, a key driver of sediment transport, still needs better characterization and understanding. This research, explores bed shear stress and near‐bed flow characteristics in sparse arrays of rigid emergent cylinders mimicking vegetation over a rough bed. For this purpose, a novel adaptation of a shear plate was used to measure bed shear stress at the canopy scale. These measurements were analyzed in relation to spatially averaged near‐bed flow quantities for different array densities. The results show that, for a constant water depth, the investigated cylinder canopy enhances the ratio between bed shear stress and bulk flow velocity (i.e., Darcy‐Weisbach bed friction factor) compared to unobstructed open‐channel flows, and that this ratio increases with array density. Moreover, higher near‐bed velocities were observed for higher array densities. On the other hand, no influence of the cylinder array on near‐bed values of turbulent kinetic energy and turbulent stresses was observed. Finally, it is shown that the thickness of the near‐bed layer is a suitable parameter to scale the ratio between bed shear stress and bulk flow velocity in vegetated rough bed flows.